Girolamo Merolla au Congo : récits de « colorisme » chez un missionnaire capucin de la fin xviie siècle - José Sarzi Amade (Multilinguales)
This article analyses some patterns within the account of the voyage to Congo made by the Capuchin missionary Girolamo Merolla. His text gives rise to a series of episodes which shed light on the encounter between two different and morally antagonistic cultures. Sometimes, this coming upon face-to-face will generate troubles, incomprehension and culture-centrist reactions. As a matter of fact, it is common to find, within the narrative of Breve e Succinta Relatione (1692), a depreciative rhetoric, imprinted with “colorism” toward Africans.